Spirituality/religiosity and psychiatry in Eugenio Borgna - Fernandes, Marcio Luiz (2021)
The article aims at demonstrating how the topic of spirituality/religiosity is developed by the Italian psychiatrist Eugenio Borgna in the horizon of phenomenological anthropology. Philosophical, theological, and literary knowledge are resources from which Borgna draws elements to meditate on questions concerning the meanings that permeate human experience in its interior dimension, such as pain, fragility, emotions, and respect for human dignity. His books are edited with name and bibliographic indexes used as a guiding map that indicates the sources that approach Borgna the most to the ultimate questions of existence. Afterward, this work identifies four categories with which it is possible to unveil Borgna’s comprehension of spirituality / religiosity: the meaning of the human, transcendence, suffering, and interiority. Finally, the article concludes that this phenomenological approach may reinforce the conscience that professionals in the health field need to be prepared for attentive listening concerning their patients’ will of meaning and spiritual demands.